A Concise Review of Pelvic Radiation Therapy (RT) for Rectal Cancer with Synchronous Liver Metastases. (21st April 2019) - Sager, Omer; Dincoglan, Ferrat; Demiral, Selcuk; Uysal, Bora; Gamsiz, Hakan; Dirican, Bahar; Beyzadeoglu, Murat
Abstract : Background and Objective . Colorectal cancer is a major health concern as a very common cancer and a leading cause of cancer-related mortality worldwide. The liver is a very common site of metastatic spread for colorectal cancers, and, while nearly half of the patients develop metastases during the course of their disease, synchronous liver metastases are detected in 15% to 25% of cases. There is no standardized treatment in this setting and no consensus exists on optimal sequencing of multimodality management for rectal cancer with synchronous liver metastases. Methods . Herein, we review the use of pelvic radiation therapy (RT) as part of potentially curative or palliative management of rectal cancer with synchronous liver metastases. Results . There is accumulating evidence on the utility of pelvic RT for facilitating subsequent surgery, improving local tumor control, and achieving palliation of symptoms in patients with stage IV rectal cancer. Introduction of superior imaging capabilities and contemporary RT approaches such as Intensity Modulated Radiation Therapy (IMRT) and Image Guided Radiation Therapy (IGRT) offer improved precision and toxicity profile of radiation delivery in the modern era. Conclusion . Even in the setting of stage IV rectal cancer with synchronous liver metastases, there may be potential for extended survival and cure by aggressive management of primary tumor and metastases in selected patients. Despite lack of consensus on sequencing of treatment modalities, pelvic RT may serve as a critical component of multidisciplinary management. Resectability of primary rectal tumor and liver metastases, patient preferences, comorbidities, symptomatology, and logistical issues should be thoroughly considered in decision making for optimal management of patients.